The Effect of Motivational Music on Recall of Routine Skills in Selected Wrestling Skills - Robabeh Rostami; Gholam Hosein Nazem Zadegan; Sousan Jabbary (رشد و یادگیری حرکتی ورزشی, 2013)
Although many researches have investigated the benefits of music in sport, few researches have studied the effect of music on movement recall. Thus, this study aimed to identify the effect of motivational music on information recall during the performance of a wrestling skill sequence. 24 male athletes (mean age 21.6±0.9 yr, height 176.4±6.1 cm and weight 67.5±8.4) were trained in 30 skills of free style wrestling during 8 weeks (2 sessions/week, 100min/session) in the acquisition phase. After 5 days of acquisition, a list of 10 skills with (1-3-2-3-1) chunk based on serial coded recall procedures were presented to the subjects and they were asked to recall and perform the list after 2 minutes. The subjects’ scores of performance were evaluated based on the main list and a score was allocated to performance sequence. Then, subjects were divided into two groups randomly. In posttest, another list was presented to the groups with the similar chunk but the only difference was that experimental group had music (BMRI form selected by subjects, MP3, 192 , tempo>120, volume 50% max of player system) concurrently with their performance. Data were analyzed by t student tests (dependent and paired and α=0.05). Findings showed that experimental group achieved higher scores in recall phase of freestyle wrestling techniques than the control group (p=0.007).It can be concluded that music as a motivational factor in recalling skill sequences can influence the performance of wrestling techniques when